POTENSI DAYA TARIK WISATA KERTHA GOSA DALAM PENGEMBANGAN PARIWISATA BUDAYA DI KABUPATEN KLUNGKUNG - Ni Putu Ayu Desi Wulandari; Ni Nyoman Raka Astrini (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
The tourist attraction of Kertha Gosa is one of the cultural heritages that has high artistic and historical value. The uniqueness of the paintings displayed on the ceiling of Bale Kertha Gosa is the hallmark of Kertha Gosa tourism which is different from other tours. Kertha Gosa which means a place for discussing everything related to the security and prosperity situation of the ancient Balinese kingdom which has a function as a meeting place for subordinate kings throughout Bali which is held every year every Purnamaning kapat day, and also as a place for Susuhunan to hold meetings with local foreigners in the Klungkung neighborhood. The existence of the Kertha Gosa tourist attraction in Klungkung Regency can be seen from the history and function of Kertha Gosa, the history and function of the existence of Kertha Gosa. In addition, the existence of the Kertha Gosa tourist attraction which is seen in terms of the potential for the beauty of architecture, history, religion, culture and the existence of the Semaranjaya museum as a place of relics of the historical objects of the King of Klungkung which is related to the existence of Kertha Gosa is the main attraction for tourists who visit Klungkung. visit and the transition of the function of Kertha Gosa from the place of the king's court to a tourist attraction.Keywords: Tourist Attraction, Kertha Gosa